Development of Triptolide Self-Microemulsifying Drug Delivery System and Its Anti-tumor Effect on Gastric Cancer Xenografts - Xie, Minghua; Wu, Jia; Ji, Liqaing; Jiang, Xiaorui; Zhang, Jin; Ge, Min; Cai, Xinjun (Frontiers in Oncology, 2019)
The objective of this study was to develop a triptolide (TP) self-microemulsifying drug delivery system and to investigate its anti-tumor effect on human gastric cancer line MGC80-3 xenografts in nude mice. The medium chain triglyceride (MCT) was selected as oil phase; polyoxyethylene castor oil (EL) was selected as surfactant, and PEG-400 was selected as cosurfactant. The mass ratio of each phase was optimized by central composite design and response surface methodology to prepare TP-SMEDDS (self-microemulsifying drug delivery system). The quality of TP-SMEDDS was evaluated, and its inhibitory effect on tumor growth investigated in nude mice transplanted with MGC80-3 cells. The final prescription process was defined as follows: MCT mass ratio: 25.3%; EL mass ratio: 49.6%; PEG-400 mass ratio: 25.1%. The prepared TP-SMEDDS was a transparent liquid with a clear appearance (average particle size: 30.46 nm). On transmission electron microscopy, the microemulsion particles were spherical in size and uniformly distributed without adhesions. The in vitro release experiment showed complete release of the prepared TP-SMEDDS in PBS solution in 6 h. In vivo antitumor activity showed its inhibitory effect in the xenograft model. Our results showed that the self-microemulsifying delivery system improved the oral bioavailability and the in vivo antitumor effect of TP.